Marriage Agreement Literacy as a Legal Protection for Indonesian Migrant Workers in Malaysia - Dina Silvia Puteri; Suhadi Suhadi; Dani Muhtada (Universitas Negeri Semarang, 2025)
Indonesian Migrant Workers (PMI) represent a vulnerable group within transnational legal systems, particularly when facing issues related to marriage and joint property abroad. The low level of legal literacy—especially concerning prenuptial and postnuptial agreements—has resulted in many migrant workers lacking awareness of their legal rights and obligations. This article aims to analyze the urgency of improving marriage agreement literacy among Indonesian migrant workers in Malaysia and to examine its relevance within the context of legal protection and social justice. This study employs a socio-legal method with an empirical approach through a community service program conducted at the Indonesian Embassy (KBRI) in Kuala Lumpur. The findings indicate that improving literacy on marriage agreements not only strengthens the legal standing of migrant workers in cross-border marriages but also serves as a preventive mechanism against potential economic and social losses resulting from legal ignorance.